Phasor Analysis of the Symmetric Crisscrossed-assisted Coupled-Ring Reflector - Gutierrez, Avram J. (Archīum Ateneo, 2023)
We investigate the general phasor characteristics of the recently reported crisscrossed coupled-ring reflector (X-CRR) and compare it with the typical coupled-ring reflector (CRR) configuration. We observe that they distinctly have different phasor features under arbitrary parameter conditions. We also (i) discuss the importance of normalized frequency range in generating the complete phasor picture of these configurations and (iii) show that in most cases the X-CRR appears to be a spread-out, rotated version of the phasor diagram of the CRR. These phasor features imply that X-CRR possesses more interesting functionalities for various potential telecom applications.